Pengaruh Price, Kualitas Produk Dan Online Customer Reviews Terhadap Keputusan Pembelian Di Shopee (Studi Pada Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Islam Malang) - Raudatul Jannah; Eka Farida; Restu Millaningtyas (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
AbstractThis study aims to determine the effect of price, product quality and online customer reviews on purchasing decisions at shopee for students of the Faculty of Economics and Business, Islamic University of Malang. The type of research applied is explanatory research using a quantitative approach. The population in this study were students of the Faculty of Economics and Business, Management Study Program, Islamic University of Malang, Class of 2018, totaling 565 students. The sample used was 85 respondents. Data collection techniques using a questionnaire. Data analysis used validity, reliability, normality, multicollinearity, heteroscedasticity, multiple linear regression analysis, coefficient of determination (adjusted R2), F test (simultaneous) and t test (partial) through SPSS 20 tools.The results showed that the price variable had a partial effect on purchasing decisions. Product quality variable has no partial effect on purchasing decisions. The online customer reviews variable has a partial effect on purchasing decisions. The variable price, product quality and online customer reviews have a simultaneous effect on purchasing decisions at shopee. Keywords: Price, Product Quality, Online Customer Reviews, Purchase Decision